Acquittal : an insider reveals the stories and strategies behind today's most infamous verdicts - Gabriel, Richard K. (Berkley Books, 2014)
"October 3, 1995. The shocking outcome of the O.J. Simpson trial leaves a nation divided. July 5, 2011. Casey Anthony walks free despite being convicted by millions on cable news and social media. There are times when something as supposedly simple as a just verdict rises to the level of cultural touchstone. Often these moments hinge on logic that seems flawed and inexplicable-until now. In Acquittal, leading trial consultant Richard Gabriel explains how some of the most controversial verdicts in recent times came to be. Drawing on more than twenty-eight years of experience, Gabriel provides firsthand accounts of his work on high-profile cases, from the tabloid trials of Casey Anthony, O.J. Simpson, Phil Spector, and Heidi Fleiss to the political firestorms involving Enron and Whitewater. An expert on court psychology and communications, Gabriel offers unique insights on defendants, prosecutors, judges, witnesses, journalists, and the most important people in the room: the jury. Through play-by-play breakdowns of the proceedings, Gabriel reveals the differences between a court of law and the court of public opinion, the convoluted mechanics behind jury selection, strategies for creating a careful balance of evidence and doubt, and the difficulties of providing a fair trial in the digital age. Along the way, Gabriel raises hard questions about not only the legal system but about the possibility of justice in an oversaturated media landscape. The courtroom is a natural theater. The stakes are high. The roles are all too familiar. And there is always the chance of a twist ending. Acquittal is a revelatory guide to this riveting, frustrating, fascinating world-the most unpredictable drama in American life"--